A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015. Issue 22 (26th August 2022) - Li, R. Y.; Wang, Z. S.; Yuan, Z. Y.; Van Horne, Constance; Freger, Viatcheslav; Lin, M.; Cai, R. K.; Chen, J. P.
Abstract: Water is one of essential resources of modern society. Employing cost-effective technologies to treat water and wastewater is of vital importance for household uses, industries and the environment. Water-stable metal-organic frameworks (MOFs) have emerged as promising innovative materials for water treatment, due to their versatility and properties such as large internal surface area, designable pore sizes, and chemical functionalities. In highly porous MOFs, metal center(s)/cluster(s) and organic ligands are linked with coordination bonds. This review paper presents the most recent developments in the industrial-scale synthesis of MOFs and applications in water purification. MOFs can be fabricated by several approaches; the microwave assisted continuous flow synthesis technologies can lead to higher production yields. The fabricated MOFs are then purified by the organic solvent and/or the solid separation, and activated by a few technologies (e.g., supercritical C O 2 ). Process safety in production, reactors design, and process optimization are important in production. The shaping techniques for MOFs on supporting materials via surface grafting/coating or embedment can be used to fabricate the MOFs-based materials with the better stability suitable for industrial applications. MOFs demonstrate much better performances than the commercially available materials in adsorption, filtration, sensing, and catalysis. Toxicity from MOFs is mainly due to the chemicals involved in the production and nano-size effects on human cells. Mitigation strategies like environmental-friendly processes for fabrication of MOFs and shaping using polymer are suggested. Various advantages from MOFs make them suitable for water treatment in the near future. Graphical abstract: UF0001